IL-7 promoted the development of thymic DN3 cells in aged mice via DNA demethylation of Bcl2 and c-Myc genes. (July 2022) - Han, Jiangyuan; Ma, Yanlin; Lv, Wei; Wang, Juan; Wu, Yu; Niu, Hongxia; Mi, Youjun; Li, Fei; Zhu, Bingdong
Abstract: IL-7 promotes the development of thymic double negative (DN) T cells during β-selection, which might contribute to the remission of aging-associated thymic involution. Methylation levels of CpG sites is correlated with aging and modulates the development. To determine the involvement of DNA methylation/demethylation instructed by IL-7 signaling during the expansion of double negative (DN) T cells, the aged mice were treated with recombinant Adeno-Associated Virus 2-mediated IL-7 (rAAV2-IL-7) and the DNA methylation/demethylation modifications in this process were analyzed. The results showed that rAAV2-IL-7 increased the number of thymocytes, especially the DN3 thymocytes during β-selection in aged mice. With aging, the methylation levels of Bcl2 and c-Myc promoter regions were increased in DN3 cells. Following rAAV2-IL-7 treatment, DNA methyltransferase Dnmt3a and Dnmt3b decreased, DNA demethylation factors TET2 and TET3 increased, and the methylation levels of Bcl2 and c-Myc in DN3 cells were reduced during DN3 stage in aged mice, consequently, resulting in the upregulation of Bcl2 and c-Myc and the larger increase of DN3 cells in thymus. In conclusion, these findings showed that Bcl2 and c-Myc genes of DN3 cells had an increased DNA methylation levels in aged mice compared to the young, and the hypermethylation in aged mice could be restored following rAAV2-IL-7 treatment. Highlights: rAAV2-IL-7 increased the number of thymocytes, especially the DN3 thymocytes during β-selection in aged mice. Ageing induced hypermethylation of Bcl2 and c-Myc, rAAV2-IL-7 decreased the corresponding methylation levels. rAAV2-IL-7 increased the expression of Bcl2  and c-Myc  by DNA demethylation in DN3 cells of aged mice. The accurate reveals of regulation mechanism at DNA level are helpful to apply IL-7 to alleviate immunosenescence in ageing.